PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI, DAN BUDAYA ETIS ORGANISASI TERHADAP KECURANGAN AKUNTANSI - Awatif, Awatif; Mulyaning Tyas, Alvy (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
This research aimed to examine the influence of the Effectiveness of Internal Control, Compensation Suitability, and Organizational Ethical Culture on Accounting Fraud. This research used a quantitative approach with primary data resources obtained from distributing questionnaires to all PT. Haryono Tours & Travel Surabaya staffs. The sampling technique used in this study is non-probability sampling using a saturated sampling method involving 28 respondents. The research questionnaire used a Likert scale with five responses rated from 1 to 5. The data processing method used multi-regression analysis utilizing SPSS software version 25. The results of this study show that the effectiveness of the internal control variable has a significant negative effect on accounting fraud, while compensation suitability and the organizational ethical culture variables do not affect accounting fraud. Then the result of this study obtained that the effectiveness of internal control, compensation suitability, and the organizational ethical culture variables simultaneously have a significant effect on accounting fraud.